SIKAP DAN PERILAKU BERAGAMA MAHASISWA UIN RADEN INTAN LAMPUNG - Jauhari, Tontowi; Mulyadi, Mulyadi (BINA' AL-UMMAH, 2017)
The objective of this research is to know the influence of family environment, school environment, campus environment, and religious attitude towards students at State Islamic University (UIN hereafter) of Raden Intan Lampung. The sample of this research was 350 students which was taken by using probability sampling technique (random sampling). The research used quantitative approach, with survey method and path analysis as an analytical tool. The results showed that the family environment, school environment, and religious attitude towards students at State Islamic University (UIN hereafter) of Raden Intan Lampung had a direct positive effect on students' behavior, and it was found that the family environment and school environment had a direct positive effect on religious attitudes, but the campus environment had no effect to students’ religious behavior, and the campus environment negatively affect the students’ religious attitude. The research findings  found that it is needed to improve the management of the family environment, the management of the school environment, and the orientation of students’ religious attitudes so that it appears a good behaviour for students of State Islamic University of Raden Intan Lampung.